تلقي المقول النقدي العربي القديم بين فعل النقل وغياب أسئلة العقل. مقاربة في نقد النقد - فيلالي, حسين (قــــــراءات; No 07-06 (2014): (مجلة قراءات( نوفمبر, 2019)
تدخل هده الدراسة في ما يعرف بنقد النقد، وتحاول أن تسلط الضوء على مقولتين نقديتين مركزيتين في النقد العربي القديم. تتعلق إحداهما بتسمية القصيدة، وببنيتها، والأخرى تتعلق بنشأة الشعر، والنثر وأيهما كان طاغيا أكثر على الثقافة العربية الكلاسيكية. تتبع الدراسة المسار التاريخي للمقولتين منذ ظهورها إلى أن وصلتا إلينا. تتبع حركتهما في كتب النقد القديم، والحديث وفي المواقع الالكترونية، لترصد كيف تعامل النقاد القدماء، والمحدثون مع المقولتين؟ وهل طرأت تغيرات على المقولتين سواء على مستوى المبنى أو المعنى؟.وهل اكتفى النقاد العرب بالنقل فقط أم عمدوا إلى التحليل وإعمال العقل؟ Abstract : This study comes within the framework of what is called the critique of criticism, and attempts to shed light on two critical essays that are pivotal in old Arabic criticism. One belongs to Ibn Rachik El Kayrawani, and is concerned with the naming of the poem and its structure, while the other, written by Al Fadl Al Rakachi, deals with the emergence of prose and poetry, and which of these was prevalent in classical Arab culture. It has been necessary to follow the historical course of the two essays from their first appearance, to the modern era. Yet following the two essays in old and modern works of criticism, as well as in websites has made it clear for us that modern critics have copied the views of the two authors literatim from their predecessors, with no questioning, comparison, discussion, or explanation. After an attempt to compare the two essays with some old critical views - we do not know why critics, modern and ancient, failed to notice it- we have come to a conclusion that agrees neither with the essays nor with other critics who took from them, which led us to propose a re-reading of the two essays.